Iron deficiency in people from a district of the province of Tayacaja, Huancavelica, Peru - Chávez Barriga, John Christian (2022)
Iron deficiency is the common pathological condition in people from low-income countries, and for its determination, ferritin and C-reactive protein should be measured to assess iron reserves. Objective: To describe iron deficiency in people from the district of Colcabamba, Tayacaja, Huancavelica. Methods: Descriptive, retrospective study. The study collected information from medical records. 164 records were collected that had serum ferritin and C-reactive protein results. Results: Of the 164 medical records reviewed, 76 and 88 are female and male, respectively; 4, 24, 81 and 55 people correspond to children under 24 months, 59 months, 10 years and 20 years, respectively; 95.73% (CI 92.33% - 99.13%) of people do not have iron deficiency. Conclusions: There is a minimum proportion of people suffering from iron deficiency in the sample evaluated.